Transparent electrostatic dissipative PC resin composition and method for producing same
The PC resin composition addresses transparency, compatibility, and heat resistance issues by using a two-step process with specific ratios and agents, achieving stable static electricity diffusion and high transparency across temperature variations.
Patent Information
- Application Number
- JP2022558433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-30
- Filing Date
- 2021-01-22
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2041-01-22
AI Technical Summary
Existing methods for creating transparent polycarbonate (PC) materials with static electricity diffusion properties face challenges in maintaining transparency, compatibility, and heat resistance, especially when temperature changes occur, and often require high amounts of antistatic agents that provide short-term effectiveness.
A PC resin composition comprising 70-95% polycarbonate resin, 5-30% antistatic agent master batch, 0.5-1.5% ester replacement inhibitor, and 1-3% auxiliary agent, processed through a two-step method to achieve improved compatibility and reduced antistatic agent dispersion phase, ensuring stability and transparency across varying temperatures.
The composition achieves a surface resistance of 10^7 to 10^10 Ω, maintaining over 85% transparency and toughness, with improved heat resistance and reduced antistatic agent usage, ensuring transparency is not affected by temperature fluctuations.
Smart Images

Figure 0007627284000001 
Figure 0007627284000002 
Figure 0007627284000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a PC resin composition and a method for producing the same, and more particularly to a transparent static electricity dissipative PC resin composition and a method for producing the same. [Background technology]
[0002] Static electricity dissipative materials have a surface resistance of 10 6 ~10 12 Ω material. Surface resistance is 10 10 ~10 12 Ω materials have the effect of preventing localized accumulation of static electricity, and their main application is in the housings of home appliances and electronic products, where they can prevent dust from sticking due to static electricity. 6 ~10 9 Ω materials have the effect of quickly dissipating static electricity, and are mainly used for preventing semiconductor failures caused by electrostatic discharge, explosion prevention, fire prevention, etc. In some cases, for example, semiconductor cases and vacuum cleaner dust collection boxes, highly transparent electrostatic dissipative materials are required.
[0003] At present, an organic polymer antistatic agent with a refractive index of 1.49 is commercially available, which can be mixed with PMMA to obtain an antistatic transparent material. In addition, a resin composition with the same refractive index as the antistatic agent can be obtained by compounding the substrate, and a transparent product can be obtained by mixing with the corresponding antistatic agent.
[0004] PC material has excellent transparency, toughness, and heat resistance, making it an irreplaceable material. When using transparent PC material and static electricity dissipation properties are required, the most common method in the industry is to apply a transparent antistatic coating layer to the surface of the PC, but the antistatic coating layer on the surface of the product obtained by this method is easily rubbed or washed off, so such static electricity dissipation properties are only effective for a short time and tend to be expensive.
[0005] By combining PC with an organic polymer antistatic agent, a static-dissipative PC material can be obtained. However, such products have three main technical problems:
[0006] (1) The refractive index range of polyether and polyamide block copolymers, which are organic polymer antistatic agents, is generally 1.48 to 1.52, while the refractive index of PC is 1.58. Since the refractive indices of the two do not match, it is difficult to obtain a transparent product by simply blending them.
[0007] (2) If PC is mixed with a resin with a low refractive index such as PMMA and the ratio of PC to PMMA is adjusted so that the refractive index is the same as that of the antistatic agent, a transparent, antistatic PC / PMMA can be obtained, but the heat resistance and impact performance of the PC will be significantly reduced, limiting the application of the product.
[0008] (3) Since the refractive index changes due to temperature are different between the organic polymer antistatic agent and other polymers, even if the product has excellent transparency at room temperature or a certain temperature, the transparency of the product will be significantly reduced when the temperature is raised or lowered.
[0009] CN101845212B discloses a transparent PC antistatic resin film, which is made by mixing PC with a polymeric antistatic agent to obtain an antistatic PC resin with a transmittance of over 88% in a 1mm thick film. However, this is only because the sample is thin, and the high transmittance is only obtained. In addition, this patent does not solve the problem of the change in transparency at different temperatures.
[0010] CN107163537B and CN110452514A disclose a method for producing transparent antistatic polycarbonate. PC is mixed with a small molecule antistatic agent (ionic liquid) to produce 10 10 ~10 12 However, such low molecular weight antistatic agents are prone to precipitation, which can cause poor antistatic properties, and are antistatic products with a short effect. Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made in consideration of the problems present in the above-mentioned prior art, such as insufficient static electricity dissipation, transparency, and the effect of temperature on transparency, and an object of the present invention is to provide a transparent, static electricity dissipative PC resin composition and a method for producing the same. [Means for solving the problem]
[0012] In order to achieve the above object, the transparent static electricity dissipative PC resin composition according to the present invention comprises, in parts by weight: Polycarbonate resin (PC resin) 70-95 parts, Antistatic masterbatch 5-30 parts, 0.5 to 1.5 parts of transesterification inhibitor, Contains the raw material ingredients.
[0013] The antistatic agent masterbatch has a mass fraction of Antistatic agent 40~60%, Transesterification promoter 0.5-1.6%, Auxiliary crosslinker 1-3%, The rest is polycarbonate resin (PC resin), Contains raw material ingredients.
[0014] The antistatic agent is an organic polymeric antistatic agent of the block copolymer type of polyether and polyamide.
[0015] The transesterification promoter is one or more selected from the group consisting of tetrabutyl orthotitanate, p-toluenesulfonic acid, and stannous octoate.
[0016] The auxiliary crosslinking agent is one or more selected from styrene-acrylonitrile grafted maleic anhydride resin, acrylonitrile-butadiene-styrene grafted maleic anhydride resin, styrene-acrylonitrile grafted glycidyl methacrylate resin, acrylonitrile-butadiene-styrene grafted glycidyl methacrylate resin, or polystyrene grafted maleic anhydride resin.
[0017] In the transparent static electricity dissipative PC resin composition, the mass fraction of the antistatic agent is 3 to 12%.
[0018] The method for preparing the antistatic agent masterbatch includes the steps of: (1) preparing a material according to the composition of raw material components of the antistatic agent master batch, and uniformly mixing each raw material component to obtain a premix; (2) The premix is charged into a twin-screw extruder, melt-extruded, cooled, and pelletized to obtain an antistatic master batch, where the extrusion temperature of the twin-screw extruder is 250-280°C, and the screw rotation speed is 200-500 rpm; The steps include:
[0019] The transesterification inhibitor is any one or more selected from tetraethyl orthosilicate, triphenyl phosphite, sodium dihydrogen phosphate, or diisooctyl phosphate.
[0020] In order to achieve the above object, a method for producing a transparent static electricity dissipative PC resin composition according to the present invention comprises the steps of: (I) preparing a material according to the blending of raw material components of a transparent electrostatic dissipative PC resin composition, and uniformly mixing the raw material components to obtain a premix; (II) feeding the premix into a twin-screw extruder, melt extruding, cooling, and pelletizing to obtain a desired product; The steps include:
[0021] The extrusion temperature of the twin-screw extruder is 240-260° C., and the screw speed is 200-500 rpm. Effect of the Invention
[0022] Compared with the prior art, the present invention has the following advantages: (1) The transparent static electricity dissipative PC resin composition obtained by the present invention not only has excellent static electricity dissipative properties and transparency, but also has a surface resistance of 10 7 ~10 10 Ω and has the excellent transparency, toughness and heat resistance of PC. The transmittance exceeds 85%, and the transparency remains stable even at different temperatures.
[0023] (2) A transparent product was obtained by improving the compatibility of the antistatic agent with PC. PC was mixed with an organic polymer antistatic agent, an ester exchange promoter and a crosslinking promoter, and the polyamide chain portion in the antistatic agent was subjected to an ester exchange reaction. At the same time, micro-crosslinking occurred between PC and polyamide due to the action of the crosslinking agent, and a polyether and PA / PC block copolymer antistatic agent masterbatch was obtained, effectively improving the compatibility of the antistatic agent with the PC resin. By blending the antistatic agent with PC, the compatibility was greatly improved, so that the dispersed phase size of the antistatic agent was significantly reduced, and when the dispersed phase size was less than half the wavelength of visible light, the blend obtained transparency.
[0024] (3) The present invention greatly reduces the amount of antistatic agent added and effectively improves the conductivity. In traditional antistatic products, the amount of organic polymer antistatic agent added is often more than 10%, and the resistance value is generally 10 9 Ω or more. However, the minimum amount of antistatic agent added in the present invention is only 3%. This is because the size of the dispersed phase of the antistatic agent is significantly reduced, the aspect ratio is increased, and the conductive path is more easily formed.
[0025] (4) The transparency of the static electricity dissipative PC material obtained by the present invention remains constant at different temperatures. In the case of conventional antistatic products, the size of the polymeric antistatic agent in the base resin is 3-800 μm, and when the temperature changes, the transparency of the material changes significantly because the refractive index change trends of the base resin and the antistatic agent are different. In the transparent static electricity dissipative PC resin composition disclosed in the present invention, the size of the dispersed phase of the antistatic agent is smaller than the wavelength of visible light, so even if the difference in refractive index between PC and the antistatic agent increases at different temperatures, the transparency of the resin composition does not change. This is ideal for static electricity dissipative products that operate under environments with changing temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will be described in detail below with specific examples. The following embodiments are useful for those skilled in the art to further understand the present invention, but do not limit the present invention. It should be noted that those skilled in the art can make some modifications and improvements without departing from the concept of the present invention, all of which belong to the protection scope of the present invention.
[0027] The transparent static electricity dissipative PC resin composition is produced in a two-stage process as follows.
[0028] (1) Preparation of antistatic agent masterbatch (1-1) Prepare the materials according to the composition of the raw ingredients of the antistatic master batch. The mass fraction of the antistatic agent is 40-60%, the mass fraction of the ester exchange promoter is 0.5-1.6%, the mass fraction of the auxiliary crosslinking agent is 1-3%, and the rest is PC resin. All the raw ingredients are uniformly mixed to obtain a premix.
[0029] (1-2) The premix is fed into a twin-screw extruder, melt-extruded, cooled, and pelletized to obtain an antistatic master batch. The extrusion temperature of the twin-screw extruder is 250 to 280° C., and the screw rotation speed is 200 to 500 rpm.
[0030] (2) Production of transparent static electricity dissipative PC resin composition (2-1) Prepare a material according to the blending of raw material components for the transparent static electricity dissipative PC resin composition. The raw material components are 70-95 parts polycarbonate resin (PC resin), 5-30 parts antistatic agent master batch, and 0.5-1.5 parts transesterification inhibitor, and are uniformly mixed to obtain a premix.
[0031] (II) The premix is added to a twin-screw extruder, melt-extruded, cooled, and pelletized to obtain the target product. The extrusion temperature of the twin-screw extruder is 240-260°C, and the screw rotation speed is 200-500 rpm. In the obtained static electricity dissipative PC resin composition, the mass fraction of the organic polymer antistatic agent is 3-12%.
[0032] Each raw material component used in this embodiment will be described below. The antistatic agent is an organic polymeric antistatic agent of the block copolymer type of polyether and polyamide. Such antistatic agents are readily available on the market, and examples include MH1657 manufactured by Arkema and Ionphase U1 manufactured by IonPhasE.
[0033] The transesterification promoter may be tetrabutyl orthotitanate, p-toluenesulfonic acid, and stannous octoate.
[0034] The auxiliary crosslinker may be a styrene-acrylonitrile grafted maleic anhydride resin, an acrylonitrile-butadiene-styrene grafted maleic anhydride resin, a styrene-acrylonitrile grafted glycidyl methacrylate resin, an acrylonitrile-butadiene-styrene grafted glycidyl methacrylate resin, or a polystyrene grafted maleic anhydride resin.
[0035] The transesterification inhibitor may be tetraethyl orthosilicate, triphenyl phosphite, sodium dihydrogen phosphate or diisooctyl phosphate.
[0036] Provided that the additives do not adversely affect the transparency and static dissipation properties of the PC resin composition, the disclosed composition may optionally further include one or more additives conventionally used in applications involving the manufacture of resin compositions. For example, the disclosed resin composition may include one or more of other resins, stabilizers, flame retardants, impact modifiers, colorants, and mold release agents.
[0037] The specific steps of carrying out the present invention are described below, and information on the antistatic agent and the like included in each embodiment and comparative example is as follows. Antistatic agent AS-1: MH1657 manufactured by Arkema, surface resistance value 109Ω Antistatic agent AS-2: Ionphase U1 manufactured by IonPhasE, surface resistance value 107 Ω. Transesterification accelerator ZJH-1: Tetrabutyl orthotitanate, commercially available Transesterification accelerator ZJH-2: p-toluenesulfonic acid, commercially available Transesterification accelerator ZJH-3: Stannous octanoate, commercially available Auxiliary crosslinker ZJL-1: Styrene-acrylonitrile grafted maleic anhydride resin, commercially available Auxiliary crosslinker ZJL-2: styrene-acrylonitrile grafted glycidyl methacrylate resin, commercially available Transesterification inhibitor YZZ-1: Tetraethyl orthosilicate, commercially available Transesterification inhibitor YZZ-3: Sodium dihydrogen phosphate, commercially available
[0038] The formulations of the antistatic agent masterbatches in the examples and comparative examples of the present invention are shown in Table 1, and the amount of each component added is expressed as a mass fraction. [Table 1]
[0039] The above antistatic agent masterbatches 1 to 8# are prepared according to the following method. (1) Weigh out the ingredients according to the weight parts shown in Table 1 and mix thoroughly to obtain a premix. (2) The premix is fed into a twin-screw extruder, melt-extruded at 260°C, and cooled to granulate.
[0040] (Examples 1 to 8) Examples 1 to 8 are transparent static electricity dissipative PC resin compositions, and the formulations are shown in Table 2, with the amount of each component added being in parts by weight. [Table 2]
[0041] (Comparative Examples 1 to 8) Comparative Examples 1 to 8 are transparent static electricity dissipative PC resin compositions, the formulations of which are shown in Table 3, with the amount of each component added being the weight content. [Table 3]
[0042] The resin compositions of Examples 1 to 8 and Comparative Examples 1 to 8 were prepared as follows. The raw materials of Examples 1 to 8 and Comparative Examples 1 to 8 were fed into a high-speed mixer and uniformly premixed to obtain a premix. The obtained premix was melt-extruded in a twin-screw extruder at an extrusion temperature of 250° C. and a screw rotation speed of 350 rpm, cooled, and pelletized to obtain a final product.
[0043] Here, in Comparative Example 4, the antistatic masterbatch was not separately prepared, but was obtained by extruding the antistatic agent, the ester exchange agent, the auxiliary crosslinking agent, the ester exchange inhibitor and the PC resin in one step according to the same composition as in Example 5. In Comparative Example 8, the PC and the antistatic agent were directly mixed.
[0044] The mechanical properties of the resin compositions prepared in Examples 1 to 8 and Comparative Examples 1 to 8 were measured. Charpy notched impact strength: Measured according to ISO179-1:2010(E) standard, impact energy was 4J. Flexural modulus: Measured according to the ISO178:2010(E) standard, the test speed was 2 mm / min. Evaluation of resistance value: The surface resistance value of the panel was measured according to ASTM D257. Light transmittance measurement: According to GB / T 2410-2008, the light transmittance of a 3 mm thick sample was measured under two environmental temperatures of 25℃ and 80℃.
[0045] Table 4 shows the test results of Examples 1 to 8, and Table 5 shows the test results of Comparative Examples 1 to 8. [Table 4] [Table 5]
[0046] Through the comparison of the examples and comparative example 4, it is very important to first prepare an antistatic masterbatch, and then mix the antistatic masterbatch with other components, that is, to prepare a transparent static-dissipative PC resin composition by a two-step method. When using a one-step preparation method, the resistance value increases significantly and the light transmittance decreases significantly. When the PC resin and the antistatic agent are directly mixed, the transmittance is only about 10%. In the examples, the light transmittance at 23°C and 80°C is not very different, while in the comparative examples, the light transmittance at different temperatures is very different. It is shown that the light transmittance of the present invention is not affected by temperature.
[0047] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and that those skilled in the art can make various changes or modifications within the scope of the claims that do not affect the essential content of the present invention.
Claims
1. In parts by weight Polycarbonate resin 70 to 95 parts, Antistatic agent master batch 5 to 30 parts, 0.5 to 1.5 parts of an ester exchange inhibitor, Contains the raw ingredients The antistatic masterbatch has a mass fraction of Antistatic agent 40-60%, Transesterification promoter 0.5 to 1.6%, Co-crosslinking agent 1-3%, The remaining amount is polycarbonate resin, Contains the raw ingredients The antistatic agent is an organic polymeric antistatic agent of a block copolymer of polyether and polyamide, and is a transparent static electricity dissipative PC resin composition.
2. 2. The transparent static electricity dissipative PC resin composition according to claim 1, wherein the ester exchange promoter is one or more selected from the group consisting of tetrabutyl orthotitanate, p-toluenesulfonic acid, and stannous octanoate.
3. 2. The transparent static electricity dissipative PC resin composition according to claim 1, wherein the auxiliary crosslinking agent is one or more selected from the group consisting of styrene-acrylonitrile grafted maleic anhydride resin, acrylonitrile-butadiene-styrene grafted maleic anhydride resin, styrene-acrylonitrile grafted glycidyl methacrylate resin, acrylonitrile-butadiene-styrene grafted glycidyl methacrylate resin, and polystyrene grafted maleic anhydride resin.
4. 2. The transparent static electricity-dissipative PC resin composition according to claim 1, wherein the mass fraction of the antistatic agent in the transparent static electricity-dissipative PC resin composition is 3 to 12%.
5. The method for preparing the antistatic agent masterbatch comprises: (1) preparing a material according to the composition of raw material components of the antistatic agent master batch, and uniformly mixing each raw material component to obtain a premix; (2) The premix is charged into a twin-screw extruder, melt-extruded, cooled, and pelletized to obtain the antistatic agent master batch, wherein the extrusion temperature of the twin-screw extruder is 250 to 280° C., and the screw rotation speed is 200 to 500 rpm; The method for producing the transparent static electricity dissipative PC resin composition according to claim 1, comprising the steps of:
6. 2. The transparent static electricity-dissipative PC resin composition according to claim 1, wherein the transesterification inhibitor is one or more selected from the group consisting of tetraethyl orthosilicate, triphenyl phosphite, sodium dihydrogen phosphate, and diisooctyl phosphate.
7. A method for producing the transparent static electricity dissipative PC resin composition according to claim 1, (I) preparing a material according to the blending of raw material components of a transparent electrostatic dissipative PC resin composition, and uniformly mixing the raw material components to obtain a premix; (II) feeding the premix into a twin-screw extruder, melt extruding, cooling, and pelletizing to obtain a target product; A method for producing a transparent static electricity dissipative PC resin composition, comprising the steps of:
8. 8. The method for producing a transparent static electricity dissipative PC resin composition according to claim 7, wherein the extrusion temperature of the twin-screw extruder is 240 to 260° C., and the screw rotation speed is 200 to 500 rpm.
Citation Information
Patent Citations
Antiflaming and antistatic modified PC (polycarbonate) / PBT (polybutylene terephthalate) alloy and preparation method thereof
CN104693745A
Polyester ester amide and resin composition
JP1995010989A
Antistatic resin composition
JP2005097598A
Transparent resin composition
JP2005154728A
Antistatic agent and antistatic resin composition
JP2016166332A